Qur’an–Hadith Teacher Personality Competence in Developing Eighth-Grade Students’ Character - Firdaus Ramadhan; Ely Surayya (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
This empirical study examined the personality competence of a Qur’an–Hadith teacher and its contribution to the character development of Grade VIII students at MTs Tarbiyah Islamiyah in Jambi City. A qualitative case study involved ten purposively selected participants: one Qur’an–Hadith teacher, one madrasah principal, and eight students representing variations in participation, academic achievement, discipline, and closeness to the teacher. Data were collected through 12 in-depth interview sessions, nine classroom observations, two observations of madrasah activities, and document analysis. Verbatim transcripts were analysed thematically through inductive–deductive coding, category development, theme review, triangulation, member checking, peer debriefing, negative-case analysis, and an audit trail. The findings indicate that consistency, fairness, emotional stability, responsibility, and willingness to correct mistakes strengthened the teacher’s moral credibility and educational relationships. However, the teacher’s influence varied: some students changed gradually, some complied only under supervision, and others reported limited influence because of family circumstances, peer pressure, previous disciplinary experiences, and individual characteristics. Discrepancies among interviews, observations, and documents show that teacher role modelling contributes to character development but is not its sole cause. The study underscores the importance of consistent institutional practices, moral reflection, habituation, and family support.